Contribución al estudio de la fisiología y el metabolismo de la bacteria ruminal Megasphaera elsdenii: uso de modelos no estructurados y análisis de flujos metabólicos - Soto Cruz, Nicolás Óscar (Universidad Autónoma Metropolitana, 2002)
Megasphaera elsu’enii is the main lactate-utilizing species in the rumen and has been considered one of the most important ruminal microorganisms. It is able to ferment up to 97% of the rumen lactate. Lactate removal is important in rumen ecology, because its accumulation causes dysfbnction such as reduced salivation, redistribution of water in the body and damage to the rumen and other tissues, among other disorders. Many important physiological characteristics of M. elsderlii grown on lactate have been established previously. It is known that: i) CO;! and the volatile fatty acids (WA) acetate, propionate butyrate and valerate are the main products of lactate metabolism, ii) M. elsdenii utilizes lactate in preference to glucose in media with both carbon sources, iii) M. elsu’enii is the only microorganism that is not subject to catabolite repression by soluble sugars, among the lactate-utilizing microorganisms known in the rumen, iv) lactate transport across the membrane appears to occur by active transport that is not dependent on Na’ or K’, among other characteristics. Although it has been reported that the production of VFA by M. elsu’enii strongly depends on the strain employed and culture medium composition, the kinetic relationship between growth and product formation has not been reported. On the other hand, about the metabolism of M. efsderlii, it is known that: i) once lactate is introduced into M. dsu’enii, lactate racemase exchanges the isomers (L and D) according to the cell requirements, ii) in the acrylate pathway, ATP, COZ, acetate and propionate are produced from lactate, iii) valerate is formed starting from an acetyl-coA and a propionyl-COA, while two molecules of acetyl-coA are condensed to produce butyrate, iv) some studies have suggested that M. elsdenii utilizes the Embden-Meyehorff-Parnas pathway and there is evidence of the utilization of the pentose phosphate pathway by M. elsdenii when it is grown in glucose. The information about other pathways of M. elsdenii biochemistry is scattered and there is no a review that gathers all this information together. Then, although some enzyme and substrate consumption studies have contributed to enhancing the knowledge of the biochemistry of M. elsdenii, there is no an integrated metabolic network. This document reviews the current knowledge about he physiology and metabolism of M. elsdenii and, using mathematical models, contributes to extend our knowledge about this bacterium during growth in lactate. Since lactate removal is important in the rumen as pointed out above, it was considered of particular interest to carry the study during lactate utilization. In this work, an unstructured model for the kinetics of growth, lactate consumption and VFA production by this ruminal bacterium was applied. The model permitted to establish the degree of association between growth, lactate consumption and VFA production under different nutritional conditions. Use of the Pirt and Luedeking-Piret equations permit the determination of the effect of medium composition on the metabolic patterns ofM. elsdenii grown in minimal and complex media with lactate as the major carbon source. In order to establish the significance of the parameters involved in the Pirt and Luedeking-Piret equations, a quantitative statistical criterion was proposed. The fitted parameters of the model suggested that, in the complex medium, lactate was completely used for growth and product formation, while in the minimal medium a fraction of the energy obtained from lactate was used for maintenance purposes. Modeling of VFA production by the Luedeking-Piret equation showed that, independent of the type of medium, acetate and propionate are growth-associated products, while butyrate and valerate are only partially growth-associated. The growth-associated products are related to energy yielding metabolism and the non growth-associated products are related to the consumption of reducing equivalents. A stoichiometric model, constituted by the acrylate, gluconeogenesis and pentose phosphate pathways, was proposed for the ruminal bacterium Megasphaera elsdenii grown in the presence of lactate. The biochemical reaction network (BRN), was proposed using information from the literature and supported by six enzyme activities, which have not been measured previously in M. elsdenii cultures. The methodologies of data consistency and metabolic flux analysis were applied to validate the stoichiometric model, which consisted of 20 metabolic reactions. Continuous cultures of M. elsder1ii were carried out in a defined medium at two dilution rates (0.05 and O. 1 h-'). Data consistency analysis applied to the black box model (C, H, O and N), allowed the validation of the quality of the experimental data. On the other hand, data consistency analysis, applied to the complete BRN, allowed the validation of the pseudo-steady state assumption for the intracellular compounds. The stoichiometric model was validated comparing the experimental measurements (L-lactate, acetate, propionate, butyrate, valerate and biomass) with the values predicted by the metabolic flux distribution calculations. Collectively, the results presented here contributed to extending our knowledge of the biochemistry of M. elsderzii grown in lactate, supporting the utilization of i) gluconeogenesis, ii) the pentose phosphate pathway and iii) a metabolic bridge constituted by the reactions of pyruvate carboxylase and phosphoenolpyruvate carboxykinase.; Megasphaera elsdenii es la principal especie consumidora de lactato en el rumen, por lo que se ha considerado uno de los microorganismos más importantes en la preservación del equilibrio ecológico ruminal. Esta bacteria es capaz de fermentar hasta el 97% del lactato presente en el rumen. La remoción de lactato es importante , ya que su acumulación causa problemas como la reducción de la salivación, redistribución de agua en el cuerpo y daño al rumen y otros tejidos, entre otros desordenes. Se conocen varias características fisiológicas importantes de M. elsdenii. Es conocido que: i) el COZ y los ácidos grasos volátiles (AGV) acetato, propionato, butirato y valerato son los principales productos del metabolismo del lactato, ii) M. elsdenii utiliza lactato en preferencia a la glucosa en medios que contienen ambas hentes de carbono, iii) M. elsdenii es, entre los microorganismos conocidos como consumidores de lactato en el rumen, el Único que no está sujeto a represión catabólica por azúcares solubles, iv) el transporte de lactato a través de la membrana parece ocurrir por transporte activo que no depende de Na' o K'. A pesar de que se ha señalado que la producción de AGV por M. elsdenii depende de la cepa empleada y de la composición del medio de cultivo, la relación cinética entre el crecimiento y la formación de productos no se ha establecido. Por otra parte, acerca del metabolismo de M. elsclenii, es conocido que: i) una vez que el lactato es introducido a la célula de M. elsdenii la lactato racemasa intercambia entre los isómeros (L y D) de acuerdo a las necesidades de la célula, ii) en la vía del acrilato, ATP, C02, acetato y propionato se producen a partir de lactato, iii) el valerato es producido a partir de un acetilCoA y un propionilCoA, mientras que dos moléculas de acetilCoA son condensadas para producir butirato, iv) algunos estudios han sugerido que M. elsdenii utiliza la vía de Embden-MeyehorfF-Parnas y existe evidencia de la utilización de la vía de las pentosas fosfato cuando M. eisdenii crece sobre glucosa. La información acerca de otras vías del metabolismo de M. eisdenii es escasa y no existe una revisión sobre el tema. Aunque algunos estudios enzimáticos y de consumo de sustratos han contribuido a ampliar el conocimiento del metabolismo de M. elsdenii, no existe una red metabólica completa. El presente documento revisa el conocimiento actual sobre la fisiología y el metabolismo de M. eisdenii y contribuye a extender el conocimiento acerca de esta bacteria, durante el crecimiento en lactato, usando modelos matemáticos. La realización de este estudio para la utilización de lactato se consideró de particular interés, debido a la importancia de la remoción de lactato en el rumen. En este trabajo se aplicó un modelo no estructurado para las cinéticas de crecimiento, consumo de lactato y producción de AGV. El modelo permitió establecer el grado de asociación entre el crecimiento, el consumo de lactato y la producción de AGV, bajo diferentes condiciones nutricionales. Se propuso la utilización de un criterio estadístico, ya establecido en la literatura, para determinar la significancia de los parámetros involucrados en las ecuaciones de Pirt y Luedeking-Piret. Los parámetros ajustados para la ecuación de Pirt indicaron que, en el medio complejo, el lactato fue utilizado completamente para el crecimiento y la formación de productos, mientras que en medio mínimo una fracción de la energía obtenida del lactato he usada para mantenimiento. El modelamiento de la producción de AGV por medio de la ecuación de Luedeking-Piret indicó que independientemente del tipo de medio utilizado, acetato y propionato son productos asociados al crecimiento, mientras que butirato y valerato son productos parcialmente asociados al crecimiento. Los productos asociados al crecimiento están relacionados al metabolismo energético y los productos parcialmente asociados están relacionados al consumo de equivalentes de reducción. Este trabajo propone un modelo estequiométrico, constituido por las vías del acrilato, gluconeogénesis y de las pentosas fosfato, para M. elsdenii creciendo en presencia de lactato. La red bioquímica de reacción (RBR), fue propuesta usando la información de la literatura y soportada por la determinación de seis actividades enzimáticas, las cuales no habían sido medidas previamente en cultivos de M. elsdenii. Las metodologías de análisis de consistencia y análisis de flujos metabólicos heron aplicadas para validar el modelo estequiométrico, el cual consiste de 20 reacciones metabólicas. Se llevaron a cabo cultivos continuos en un medio definido a dos tasas de dilución (0.05 y O. 1 h-'). El análisis de consistencia, aplicado al modelo de caja negra (balances de C, H, O y N), permitió la validación de la calidad de los datos experimentales. Por otra parte, el análisis de consistencia, aplicado a la RBR, permitió validar la suposición de estado pseudoestacionario para los compuestos intracelulares. El modelo estequiométrico fue completamente validado comparando las mediciones experimentales (L-lactato, acetato, propionato, butirato, valerato y biomasa) contra los valores predichos por la distribución de flujos metabólicos. En su conjunto, los resultados presentados contribuyen a extender el conocimiento de la bioquímica de M. elsdenii creciendo sobre lactato, soportando la utilización de la gluconeogénesis, la vía de las pentosas fosfato y un puente metabólico constituido por las reacciones de la piruvato carboxilasa y la fosfoenolpiruvato carboxicinasa.